The welfare we want? : The British challenge for American reform - Wiseman, Michael; Walker, Robert, 1949- (Book collections on Project MUSE., 2003)
The welfare we want? presents a detailed and unique comparison of welfare policies in the Britain and America. A team of international experts outlines, compares and contrasts the reform strategies pursued in each country and summarises the results to date.